INDUSTRIAL TRENDS, CHALLENGES & OPPORTUNITIES IN THE FIELD OF AUGMENTED & VIRTUAL REALITY - Anil G. Naik; Anurag Reddy, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2023)
Augmented reality and virtual reality (AR/VR) technologies have the potential to revolutionize the way we work, learn, and interact with the world. Advances in computing platforms and connectivity have helped accelerate this growth. This paper provides a quick overview of AR/VR technologies and their importance in various aspects of our lives. Moreover, their current and future opportunities to be adopted in healthcare, education, entertainment, real-time communication, military, and others are discussed. In addition, the future trends of these technologies in the coming decades are discussed with respect to market size and growth rates. Furthermore, the broad challenges and limitations that these technologies should face in the near future are also highlighted. In addition to advancements in AR/VR hardware and connectivity, the development of artificial intelligence (AI) and machine learning (ML) will play a crucial role in advancing AR/VR technology. The adoption of AR/VR technologies is growing rapidly as more businesses and industries recognize the potential benefits of these technologies. The key factor for growth is overcoming AR/VR technology adoption barriers via continuous financial investment for innovations, advances in computing platforms, and connectivity to accelerate market growth. The future of AR/VR appears promising; thus, more innovative applications and use cases will be predicted in the coming years.